Thermophysical Properties of Cryoprotective Agents. III. Density, Kinematic Viscosity and Surface Tension of Some Cryoprotective Agents, Their Solutions and Mixtures - Todrin, A. F.; Popivnenko, L. I. (Problems of Cryobiology and Cryomedicine, 2011)
The literature data for density, kinematic viscosity and surface tension values, pure cryoprotective agents, their solution and mixtures are summarized. The empiric polynomial equations for calculation of density, kinematic viscosity and surface tension of water, pure cryoprotective agents, their aqueous solutions and mixtures depending on temperature and concentration are derived.